STRATEGI SUSTAINABLE MARKETING MIX DAN GREEN ATTITUDE TERHADAP CUSTOMER LOYALTY ECO-FRIENDLY COFFEE SHOPS - Andini, Kianita Putri; Dwi Retno Andriani; Agustina Shinta Hartati Wahyuningtyas (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2026)
Environmental issues are one of the focuses of business and consumer issues. Thus, companies need to implement sustainability aspects to increase consumer loyalty through sustainable marketing strategies (Eirene, 2024). Consumers also need to build a green attitude to care more about environmental sustainability through the consumption of green products. The application of sustainable marketing applies to coffee shop businesses due to increasing demand and high competition in increasingly competitive coffee shops in Indonesia. Eco-friendly coffee shop MSMEs experience obstacles in implementing sustainable marketing due to limited resources, greater effort and costs, high price competitiveness, and many customer complaints. This study aims to analyze the influence of sustainable marketing mix strategies directly and indirectly through the mediation of brand image, green brand awareness, and customer satisfaction on customer loyalty and the influence of green attitudes on customer loyalty of eco-friendly coffee shops. This study was conducted in UMKM eco-friendly coffee shops through a quantitative approach and a non-probability sampling method through convenience sampling on 205 respondents. The data analysis method used PLS-SEM analysis with WarPLS 8.0 software. The results of this study indicate that a sustainable marketing mix and green attitude have a direct positive effect on customer loyalty. However, a sustainable marketing mix does not have an indirect effect through mediation on customer loyalty to eco-friendly coffee shops. Thus, eco-friendly coffee shops can optimize the implementation of sustainable marketing strategies that can improve brand image and green brand awareness and then affect customer satisfaction and loyalty as well as the sustainability of eco-friendly coffee shops in the long term and innovate product attributes to increase loyalty through the influence of high consumer green attitudes so that they can meet consumer needs.